Impact of NRM research - the way forward - Macours, Karen (2018)
Karen Macours Policy Seminar Managing natural resources for sustainable production systems: A research agenda at the crossroads Co-organized by CGIAR Independent Science and Partnership Council (ISPC); IFPRI; and CGIAR Research Program on Policies, Institutions and Markets Feb 28, 2018 - 12:15 pm to 01:45 pm EST